STUDY AND VALIDATION OF MESHES IN TURBULENT ISOTHERMAL PROBLEMS OF NATURAL CONVECTION IN FLAT PLATES - Silva, V. R.; Verdério Júnior, S. A.; Caminaga, C.; Neves, R. C. M. (Revista de Engenharia Térmica, 2021)
The study of natural convection on flat plates is of great interest in the areas of Engineering, both for the simplicity of geometry and the wide variety of applications. In the study and definition of a numerical model, an ideal mesh configuration is the one that best represents physically, with minimal numerical influence and with the lowest computational cost, the problem addressed. The influence of two mesh configurations (non-uniform staggered and entirely uniform), at different refinement levels, was studied to evaluate natural convection heat transfer rates in flat plates of AR = 5; in isothermal conditions, in turbulent regime with the κ−ω SST RANS model and using free and open-source software OpenFOAM®. The physical-numerical methodology applied, and the numerical results obtained were validated from experimental results in the literature. The non-uniform staggered mesh configuration proved to be more adequate in precision, and computational cost to the problem situation studied. The entirely uniform mesh proved to be infeasible due to the high number of elements and computational cost demanded.